Residual inflammatory risk at 12 months after acute coronary syndromes is frequent and associated with combined adverse events. (March 2021) - Klingenberg, Roland; Aghlmandi, Soheila; Gencer, Baris; Nanchen, David; Räber, Lorenz; Carballo, David; Carballo, Sebastian; Stähli, Barbara E.; Landmesser, Ulf; Rodondi, Nicolas; Mach, François; Windecker, Stephan; et al.
Abstract: Background and aims: Residual inflammatory risk (RIR) after acute coronary syndromes (ACS) may identify patients likely to benefit from anti-inflammatory therapies. Methods: Patients from the Special Program University Medicine ACS cohort were divided into four groups according to level of hsCRP at baseline and after 12 months: persistently high RIR, increased RIR (first low, then high hsCRP), attenuated RIR (first high, then low hsCRP), or persistently low RIR. High RIR was defined as hsCRP ≥ 2 mg/L. An independently adjudicated incident of combined adverse events was defined as the composite of myocardial infarction, clinically indicated coronary revascularization or cerebrovascular events. Results: Among 1209 patients with available hsCRP, clinical and demographic data, 295 (24.4%) patients had persistently high RIR (delta hsCRP median (IQR): 2.3 (−9.9; 0.3) (mg/L) and 72 (5.96%) patients had increased RIR (delta hsCRP median (IQR): +2.45 (1.2; 8.35) (mg/L). A total of 390 (32.26%) patients had attenuated RIR (delta hsCRP median (IQR): 3.55 (−10; −2) (mg/L) and 452 (37.38%) patients had persistently low RIR (delta hsCRP median (IQR): 0.2 (−0.6; 0.1) (mg/L). Of 90 combined adverse events, 31 (10.5%) occurred in the persistently high (multivariable adjusted OR: 1.71, (95% CI 1.08–2.7), p  = 0.022) compared with the three other groups combined (increased RIR: 3 (4.2%), attenuated RIR 30 (7.7%), persistently low RIR 26 (5.8%). Conclusions: Persistently elevated hsCRP after ACS is found in a quarter of patients with the highest risk of combined adverse events. This underlines the need to perform anti-inflammatory intervention trials in RIR patients. Highlights: At 12 months after an Acute Coronary Syndrome a quarter of patients had persistently increased hsCRP (≥ 2mg/L), experiencing more adverse events. Patients in this category of persistently high residual inflammatory risk are likely to benefit from anti-inflammatory therapies aimed at pathways upstream of CRP.